Re‐ordering Motherhood and Employment: Mobilizing 'Mums Everywhere' during Covid‐19. (22nd June 2022) - Ashman, Rachel; Radcliffe, Laura; Patterson, Anthony; Gatrell, Caroline
Abstract: This paper explores the impact of the 'mobilization' of employed mothers by the UK government to home‐school and care for children while performing paid work at home, in order to limit Covid‐19 transmission. Drawing upon actor network theory (ANT), we extend John Law's (1994) concept 'modes of ordering' (or strategic shifts in response to change when power relations are unequal) to illuminate how employed mothers' networks were re‐ordered. In this netnography, we observe how they re‐ordered personal and local networks to combine home‐working, home‐schooling and childcare. We learn how, when mothers' usual networks broke down, they employed three novel modes of re‐ordering: retentive, retrogressive and reformative. These modes capture the complex relationships between work and family – an area of concern that has previously received limited attention in relation to actor networks. Our findings reveal the gendered nature of the mandatory imposition of home‐working during the pandemic. Through developing Law's modes of ordering, we demonstrate the potential of ANT to understand the impact on mothers of home‐working and highlight important practical contributions for organizations and governments.